2011
DOI: 10.1002/hyp.8055
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of precipitation in Haihe River Basin, China: six decades of measurements

Abstract: Abstract:This study aims to determine temporal trends and spatial distribution of the annual and monthly precipitation in the Haihe River Basin, China, during 1951China, during -2008. A significant decreasing trend was observed for the annual precipitation, mainly attributed to the abrupt decrease in the flood-season precipitation (June-September) around the year of 1979. No significant trend was revealed for precipitation within Period I of 1951-1979 and Period II of 1980 Results of this study indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…The existence of a statistical significant breakpoint indicates that the study period should be segmented into sub‐periods for trend analyses and other investigations. This approach was widely used for similar studies on hydrology and climatic change in many regions [e.g., Partal and Kahya , 2006; Smadi and Zghoul , 2006; Wang et al , 2009; Zheng et al , 2009; Wang et al , 2011]. The existence and significance of a breakpoint may vary with the study locations and periods.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of a statistical significant breakpoint indicates that the study period should be segmented into sub‐periods for trend analyses and other investigations. This approach was widely used for similar studies on hydrology and climatic change in many regions [e.g., Partal and Kahya , 2006; Smadi and Zghoul , 2006; Wang et al , 2009; Zheng et al , 2009; Wang et al , 2011]. The existence and significance of a breakpoint may vary with the study locations and periods.…”
Section: Methodsmentioning
confidence: 99%
“…The precipitation influenced by the East Asia monsoon decreases from southeast to northwest, and approximately 70-80% of precipitation occurs during the monsoon season from June to September (Chen, 1999). Snow contributes the majority of the precipitation in winter, but generally melts in 2-3 weeks (Wang et al, 2011b). The mean annual pan evaporation ranges from 1100 to 2000 mm (Chen et al, 2005), which is measured by the diameter 20 cm of the evaporation pan.…”
Section: Study Areamentioning
confidence: 99%
“…Trenberth et al [16] found that there were increases in temperatures and sea surface temperatures along the western coast of North America and Alaska, as well as changes in coastal rainfall and streamflow. In China, Wang et al [17] found an abrupt decrease in the flood-season precipitation around the year of 1979 based on weather stations in the Haihe River Basin. Zhao et al [18] confirmed an abrupt decrease in precipitation during the late 1970s and middle 1980s was also observed in the upper Yellow River Basin.…”
Section: Introductionmentioning
confidence: 99%